The neural mechanisms of general anesthesia - Zarith Fadila, Jamel (Universiti Malaysia Sarawak, UNIMAS, 2009)
This study aims to analyze, assess and synthesize other research works on the neural mechanism of general anesthesia. The main focus of this study is to investigate the region of the brain involved in the induction of general anesthesia and the neural mechanisms of general anesthetics that induce general anesthesia, based on the experiments and primary research carried out by other researchers. The results of experiments and findings from other researchers are gathered and analyzed to see how the results of the experiments may conform or contradict each other. The parts of the brain involved in general anesthesia are identified. The neural mechanism of general anesthesia is better understood as well. From the extensive discussions in this research, it is found that thalamus, brainstem and reticular formation are the main targets of anesthetics. In terms of neural mechanism, general anesthetics exert its actions by altering neural functions and activites, causing the signal in the brain to be desynchronized.